Freshwater Fish of New River, Belize - Venetia Briggs-Gonzalez; Kyle Allen; Frank J. Mazzotti (EDIS)
Belize is home to an abundant diversity of freshwater fish species and is often considered a fishing paradise. The New River area is a popular freshwater fishing destination in the Orange Walk district of northern Belize. Here locals and visitors alike take to the lagoons and waterways for dinner or for good sportfishing. This 3-page guide highlights the most popular species in the area and will help people identify and understand these species. Written by Venetia Briggs-Gonzalez, Kyle Allen, and Frank J. Mazzotti, and published by the Wildlife Ecology and Conservation Department, November 2015.